Investigating factors affecting knowledge management and sharing on innovation in universities: pilot study - Haque, Mohammad Mozammel; Ahlan, Abdul Rahman; Mohamed Jalaldeen, Mohamed Razi; Subiyakto, A'ang (IEEE Xplore, 2017)
Factors that influence knowledge management (KM) and knowledge sharing (KS) have many potential benefits in the decision-making process for augmenting organizational performance. The main purpose of this study is to examine the antecedent factors that predominately influence academics' Knowledge management and sharing (KM&S) intention for universities KM practices. The study primarily investigates how and which individual, organizational and technological factors impact on academics' KS intention. This study has commissioned a Pilot phase with a quantitative technique using PLS-SEM method, deploying IS theory in its research framework. The study empirically assessed using survey data that was collected from 100 academics in two leading public universities in Bangladesh. The study analyzed both Structural model and Measurement model and tested hypotheses. The findings of this study have revealed that 9 out of 12 constructs have influenced significantly on academics' KM&S intention upon universities innovation.